Interference from cloud-to-ground and cloud flashes in wireless communication system - Ahmad, Mohd Riduan; Mohd Esa, Mona Riza; Cooray, Vernon; Dutkiewicz, Eryk (ELSEVIER, 2014)
In this study, cloud-to-ground (CG) flash and cloud (IC) flash events that interfere with the transmission of bits in wireless communication system operating at 2.4 GHz were analyzed. Bit error rate (BER) and consecutive lost datagram (CLD) measurement methods were used to evaluate BER and burst error from 3 tropical thunderstorms on November 27, 28, and 29 during 2012 northeastern monsoon in Malaysia. A total of 850 waveforms from the electric field change recording system were recorded and examined. Out of these, 94 waveforms of very fine structure were selected which matched perfectly with the timing information of the recorded BER. We found that both CG and IC interfered significantly with the transmission of bits in wireless communication system. The interference level becomes worst as the number of return strokes (RSs) increases and the intensity of the flash intensifies. Narrow bipolar pulses (NBP) event is suggested to radiate the most intense microwave radiation pulses, larger than preliminary breakdown process (PBP) and typical IC flash and caused more severe burst error to wireless communication system. In CG flash, PBP event is suggested to radiate the most intense microwave radiation pulses that interfered with the bits transmission and caused significant burst error. RSs are suggested to radiate less intense microwave radiation but still interfere with the bits transmission and cause significant burst error especially when the number of RSs becomes larger. Furthermore, we found that the typical IC pulses interfered the bits transmission in the same way as PBP in CG flash and produced comparable amount of burst error.